Post-COVID Syndrome: Impact, Investigation Strategies and New Treatment Methods for Students with Disabilities - Eliyas, Andri; Rochyadi, Endang; Aprilia, Imas Diana (Proceeding of International Conference on Special Education in South East Asia Region, 2023)
The COVID-19 pandemic has affected people with disabilities in a number of ways, including the development of post-COVID syndromes. Post-COVID syndrome is a condition that affects individuals who have recovered from COVID-19 but continue to experience a variety of symptoms, such as fatigue, shortness of breath and cognitive impairment. This article examines the impact of post-COVID syndrome on students with disabilities and reveals new investigations and treatment methods for post-COVID syndrome. This study uses the literature review method. This study found that post-COVID syndrome can significantly affect the academic performance and mental health of students with disabilities, requiring a multidisciplinary treatment approach. This article recommends implementing an individualized support plan, including accommodation, mental health services, and physical rehabilitation, to address the unique needs of each student with post-COVID syndrome. It also emphasizes the importance of further research to improve understanding of post-COVID syndromes in people with disabilities.